ACCESSIBILITY FOR PERSONS WITH DISABILITIES IN CREATING INCLUSION-BASED SERVICES IN THE ASIAN-AFRICAN CONFERENCE MUSEUM - Jamilah, Asyfiya Qurratal; Zulaikha, Sri Rohyanti (Jurusan Pendidikan Luar Biasa, 2021)
This article discusses the importance of museum accessibility for people with disabilities, especially in the context of the Asian-African Conference Museum (KAA) in Bandung, Indonesia. This research aims to determine the accessibility of the KAA Museum in its efforts to demonstrate social inclusion, especially for people with disabilities. The research method uses a descriptive qualitative approach to explore the challenges, efforts and impacts of accessibility on museum visitors. The KAA Museum emphasizes its commitment as a